Ruptured Intramural Pregnancy with Low and Declining β-human Chorionic Gonadotropin Levels - Yu-Hung Lin; Kok-Min Seow; Lee-Wen Huang; Jiann-Loung Hwang (Elsevier, 2005)
Objective: Intramural pregnancy is the rarest type of ectopic pregnancy and its diagnosis is usually not made until surgery. This case of intramural pregnancy had an unusual course and an ultrasound appearance not previously reported. Case Report: A 29-year-old woman presented with vaginal bleeding. Ultrasound revealed an empty uterus and a heterogeneous mass at the fundus that displayed prominent blood flow on color Doppler and power Doppler ultrasound. Initial serum β-human chorionic gonadotropin (β-hCG) level was 441 mIU/mL and dropped to 295 mIU/mL 2 days later. The woman, however, had heavy vaginal bleeding on the following day. The mass was excised at emergency laparotomy. The pathologic report confirmed the diagnosis of intramural pregnancy. Conclusion: Intramural pregnancy may appear as a heterogeneous mass with prominent blood flow on Doppler ultrasound. The possibility of rupture should be kept in mind even if serum β-hCG is low and keeps falling.